2008
DOI: 10.1007/s12272-001-1192-7
|View full text |Cite
|
Sign up to set email alerts
|

A convenient preparation of a disaccharide motif and its role in the cytotoxicity of the triterpenoid saponin, α-hederin

Abstract: The sugar structures of triterpenoid saponins, such as alpha-hederin, are intimately associated with their antitumor activities and other biological activities. The alpha-L: -rhamnopyranosyl-(1-->2)-alpha-L: -arabinopyranoside group of alpha-hederin alters the cytotoxicity of its aglycon, hederagenin. This study explored the role of this saccharide unit in the cytotoxic effect of alpha-hederin and the possibility of its use as a carrier moiety in prodrugs of anticancer agents. A new convenient and practical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…With its strong anticancer effect and multiple anticancer mechanisms, α-hederin may potentially become a more reliable anticancer drug. However, due to its strong toxicity (54-57), protein absorption (58) and hemolytic effect (59), further molecular modifications and nanotarget drug carriers should be applied during the anticancer study of α-hederin.…”
Section: Discussionmentioning
confidence: 99%
“…With its strong anticancer effect and multiple anticancer mechanisms, α-hederin may potentially become a more reliable anticancer drug. However, due to its strong toxicity (54-57), protein absorption (58) and hemolytic effect (59), further molecular modifications and nanotarget drug carriers should be applied during the anticancer study of α-hederin.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, not much information is available about the influence of α-HN on the SKOV-3 ovarian cell line [20] and also no data are available about the mechanism underlying this effect.…”
Section: Discussionmentioning
confidence: 99%
“…α-HN is also active against other cell lines, for instance: Lewis lung carcinoma (LL/2), smooth muscle (HASM), human kidney (HEK293), and transfected HEK293 cell lines [18,19]. With regard to colon cancer (HT-29), α-HN is claimed to act synergistically with 5-fluorouracil and 3- O -α- l -rhamnopyranosyl-(1→2)-α- l -arabinopyranoside [20,21]. Furthermore, α-HN was also tested in comparison to its chitosan nanoparticles (α-HN-CS-CD147-NPs) on human liver cancer cell lines SMMC-7721 and HepG2 and it was found that the antibody when coupled with α-HN became more active against these cell lines than α-HN alone [22].…”
Section: Introductionmentioning
confidence: 99%
“…Saponin exhibits anti-microbial activity and has a lytic effect on erythrocyte membrane [73]. It has also demonstrated hypoglycemic effect [74] and lowering of serum cholesterol levels in animals [75] [76]. Saponins reduce protein digestibility by the formation of sparingly digestible saponin-protein complexes [77].…”
Section: Active Secondary Metabolitesmentioning
confidence: 99%